The Republican Alternative The Netherlands and Switzerland Compared - Prak, Maarten; Maissen, Thomas; Holenstein, André (Amsterdam University Press, 2008)
The Netherlands and Switzerland are among the world's most economically successful societies. Their inhabitants enjoy high standards of living and express great satisfaction with their lives according to surveys. This despite serious natural handicaps, such as a lack of raw materials and an abundance of water and rock respectively. The foundation for their prosperity was laid in the early modern period, between roughly 1500 and 1800, when, as federal republics, the two countries were already something of an anomaly in Europe. Their inhabitants experienced serious anxieties and tried to justify their exceptionality, to which they were, at the same time, greatly attached. The Republican Alternative attempts to clarify, through a sustained comparison, the special character of the two countries, which were similar perhaps at first sight, but nonetheless developed their own solutions to the challenges they faced. The book includes in-depth discussions of citizenship arrangements, Swiss and Dutch dealings with religious pluriformity, political discourses justifying the republican form of government, the advantages and disadvantages of an agrarian over a commercial society.